Arabic Vocabulary Acquisition Through Food Knowledge in Lower Grades at Sanggar Bimbingan Srimuda, Kuala Lumpur, Malaysia - Zaifatur Ridha; Savira Fatimah Zahrani; Nur Aisyah (International Journal of Islamic Educational Research, 2025)
This study aims to improve Arabic vocabulary acquisition in lower grade students through a food knowledge-based approach at Srimuda Guidance Centre, Kuala Lumpur. Arabic as the language of the Qur'an is very important to learn from an early age, but its learning is often considered difficult by children due to non-contextualised methods. To overcome this, this research uses a qualitative approach with a case study type. Data were collected through participatory observation, semi-structured interviews, and documentation during the learning activities that took place in three sessions. Each session involved the introduction of food vocabulary in Arabic through activities such as matching pictures, drawing favourite foods, role-playing as sellers and buyers, to simple quizzes. The results showed that students were more enthusiastic and able to remember and mention at least five food vocabulary words in Arabic correctly. The use of real media and interactive activities is proven to make children understand and absorb new vocabulary faster because it is in accordance with their cognitive development stage. This study concludes that learning Arabic vocabulary with a food theme approach can be an effective, fun and contextualised method for early childhood. The implication of this study can be used as a reference in developing Arabic language teaching methods in non-formal and formal educational institutions at the early age level.